The Blood Glucose Regulation in Intensive Care Unit (ICU) - Andriani, Ika Jati Setya; Jufan, Ahmad Yun (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Glucose control among ICU patients has been a topic of debate over the past 20 years. Harmful effects posted by uncontrolled hyperglycemia and hypoglycemia among critically-ill patients have been acknowledged widely. Previous researches had proven that a tight glucose control is not only of no benefit, but instead harmful due to the increased risk of developing a significant hypoglycemia. Current guidelines suggest a moderate approach of intravenous insulin therapy initiation towards critically-ill patients with blood glucose level above 180 mg/dL. The most integral factor that underlies the glycemic management of patients in the ICU is the prevention of hypoglycemia. A robust glucose monitoring and insulin protocol strategies need to be implemented in achieving this goal. Keywords: glucose control, hyperglycemia and hypoglycemia, ICU